Kegiatan Pendampingan dalam Meningkatkan Penjualan Pada Badan BUMDES Barokah Kecamatan Gadingrejo Kabupaten Pringsewu - Eliza Delicia; Dwi Asri Siti Ambarwati; Nindytia Puspitasari Dalimunthe; Sri Hasnawati; Aida Sari (BADAN PENERBIT STIEPARI PRESS, 2023)
Bumdes Barokah is a village business entity that operates in the business of selling goats. Since April 2021, BUMDes Barokah has experienced difficulties in generating income. This causes BUMDes Barokah not to run as expected so there was a need for a business strategy so that business activities at BUMDes could develop and BUMDes could achieve the desired results. The aim of this activity is to assist BUMDES in finding and implementing the right business strategy to increase sales. The technique used to find the right business strategy is by using SWOT analysis and the Business Model Canvas (BMC). The results of the SWOT analysis found that sales outside of holidays were low and there were competitors who could threaten the BUMDes goat sales business. It is hoped that the results of this activity can be an input for BUMDes in terms of business strategies to increase sales at BUMDes Barokah.